Analisis Status Kesuburan Tanah Pada Lahan Pertanian Di Kelurahan Lambanapu Kecamatan Kambera Kabupaten Sumba Timur - Mila, Sartini; Nganji, Marten Umbu; Lewu, Lusia Danga; Kapoe, Suryani K.K.L; Pari, Aris Umbu Hina; Taranau, Ospensius Kawawu (Sandalwood Journal Of Agribusiness And Agrotechnology, 2024)
Lambanapu Village is one of the villages that is a production center for horticultural and food crops. Paddy rice, corn, vegetable horticulture and fruit horticulture are common crops developed in Lambanapu Village. However, crop productivity has decreased due to erratic climatic conditions. In addition, another factor that determines the decline in crop productivity is the occurrence of flash floods and a decrease in soil quality. The availability of nutrients in the soil that are sufficient to support plant growth has a close relationship with the soil fertility of agricultural land. This study aims to determine the status of soil fertility on agricultural land in Lambanapu Village. The method used was survey method of soil sampling based on purposive sampling method. The results obtained on the content of P-available 9.26 - 23.09, K-available 37.34 - 50.17, base saturation 70.05 - 77.63, C-organic 1.65 - 1.94%, Cation Exchange Capacity 27.61 - 33.13. Based on the matching results of laboratory analysis with soil fertility status criteria, two soil fertility statuses were obtained in Lambanapu Village, namely low and medium soil fertility status. Low soil fertility status is at observation points T4,T5,T6,T7,T8,T9,T10, while medium soil fertility status is at observation points T1,T2,T3. Improvement efforts that can be done to improve soil fertility status on the research site is by adding organic matter to the soil in order to maintain and improve soil fertility.